Year-long monitoring of phytoplankton community, toxigenic cyanobacteria, and total microcystins in a eutrophic tropical dam supplying the Mexico megacity - Martínez-Jerónimo, Fernando; Antuna-González, Paloma del Carmen; Hernández-Zamora, Miriam; Martínez-Jerónimo, Laura; Munoz, Gabriel; Simon, Dana F.; Sauvé, Sébastien (Frontiers in Environmental Science, 2022)
The Valle de Bravo dam is an important source of drinking water supply for the Mexico City Conurbation (>26 million inhabitants) and is also a hotspot for nautical sports, recreational fishing, and tourism. However, anthropogenic pressures in the upper reaches of the basin have led to increased eutrophication and numerous harmful cyanobacterial blooms (HCBs). To determine the effect of abiotic variables on the characteristics of the phytoplanktonic community, as well as their influence on the diversity of toxigenic cyanobacteria and related cyanotoxins, we evaluated monthly variations in environmental factors, phytoplankton biovolume and composition, and total microcystins in Valle de Bravo dam during the year of 2019. Overall, 75 phytoplanktonic species were identified, mostly belonging to the divisions Cyanobacteria, Chlorophyta and Bacillariophyta. Cyanobacteria presented the highest biomass throughout the year, with water temperature and rainfall being the best correlated factors. The highest concentrations of total microcystins were recorded from July to September (maximum of 71 μg L-1), associated with the dominance of species such as M. smithii, M. aeruginosa, M. viridis M. flos-aquae, Aphanocapsa planctonica, and Dolichospermum crassum, and environmental factors such as rainfall, total dissolved solids, water temperature, and specific trace metals. In all months except December, the total cyanobacterial biovolume was above the World Health Organization alert level 2, indicating potentially high risks to human health. The predominance of cyanobacteria and high biovolumes classified water quality as poor to very poor during most of the year. Control measures are required to improve the trophic status of the reservoir and reduce health risks related to HCBs and cyanotoxin exposure.